Hepatitis B and Hepatocellular Carcinoma: A Case Report and Literature Review - Rendi Aji Prihaningtyas; Muhammad Irawan; Qurrota Ayuni Novia Putri; Bagus Setyoboedi; Sjamsul Arief (MEDICINUS, 2025)
Introduction: Current data estimates that over 90% of primary liver tumors are hepatocellular carcinomas (HCC), a type of malignant hepatocyte tumor. Viral hepatitis B is particularly associated with HCC. Early detection of chronic hepatitis B is crucial to prevent complications. Case Presentation: A 17-year-old girl presented with a one-month history of abdominal enlargement, jaundice, dark urine, and pale-colored stool. She experienced weight loss and a lack of appetite. Anthropometric assessment indicated severe malnutrition. The abdomen appeared distended with ascites. There was a palpable liver, with a firm consistency and a lumpy surface up to the epigastrium, with a size of 8 x 7 x 6 cm, and accompanied by splenomegaly. Laboratory examination indicated anemia (hemoglobin 9.5 g/dl), white blood cells 12.38 x 10³/μl, platelets 859 x 10³/μl, AST 1,095 U/l, ALT 104 U/l, cholestasis (total bilirubin 66.5 mg/dl and direct bilirubin 4.14 mg/dl), hypoalbuminemia (albumin 2.81 g/dl), LDH 3146 U/l, reactive HBsAg >1,000, AFP >1,000 ng/ml. An abdominal ultrasound revealed hepatomegaly with multiple nodules distributed across nearly all liver segments, and some of which formed a mass measuring 7.9 x 6.4 x 5.8 cm in the right lobe. Additionally, splenomegaly and ascites were observed. CT scan of the abdomen showed masses distributed throughout the hepatic lobe with contrast enhancement in the arterial phase and feeding from hepatic artery, in the venous phase, contrast washout with ascites. These findings support the diagnosis of hepatocellular carcinoma. Conclusion: Children with HBV may have had prior medical visits without being accurately diagnosed, representing missed opportunities for timely HBV detection. There is a critical need for increased awareness and early screening for hepatitis B virus (HBV) infection in children, especially in regions where HBV prevalence is high.